Spring reproductive success influences autumnal malarial load in a passerine bird - Pigeault, Romain; Cozzarolo, Camille-Sophie; Wassef, Jérôme; Gremion, Jérémy; Bastardot, Marc; Glaizot, Olivier; Christe, Philippe (Peer Community Journal, 2024)

(untitled)
Although avian haemosporidian parasites are widely used as model organisms to study fundamental questions in evolutionary and behavorial ecology of host-parasite interactions, some of their basic characteristics, such as seasonal variations in within-host density, are still mostly unknown. In addition, their interplay with host reproductive success in the wild seems to depend on the interaction of many factors, starting with host and parasite species and the temporal scale under study. Here, we monitored the parasitemia of two haemosporidian parasites – Plasmodium relictum (lineage SGS1) and P. homonucleophilum (lineage SW2) – in two wild populations of great tits (Parus major) in Switzerland over three years, to characterize their dynamics. We also collected data on birds’ reproductive output – laying date, clutch size, fledging success – to determine whether they were associated with parasitemia before (winter), during (spring) and after (autumn) breeding season. Parasitemia of both species dramatically increased in spring, in a way that was correlated to parasitemia in winter. Parasitemia before and during breeding season did not explain reproductive success. However, the birds which fledged the more chicks had higher parasitemia in autumn, which was not associated with their parasitemia in previous spring. Our results tend to indicate that high haemosporidian parasite loads do not impair reproduction in great tits, but high resource allocation into reproduction can leave birds less able to maintain low parasitemia over the following months.